CHARACTERISTIC ANALYSIS OF BEARING CAPACITY WITH LABORATORY CALIFORNIA BEARING RATIO TEST AND UNCONFINED COMPRESSION STRENGTH TEST - Arfan, Muhammad; Setiawati, Mira (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2018)
Construction carried out on soft soil must require serious handling such as selection of the right type or type of foundation or soil improvement. However, during this time the investigation of soil in soft soil areas often has difficulty, the difficulty is the difficulty of obtaining undisturbed samples and the difficulty of testing the physical properties of soft soil including testing the strength of the soil bearing capacity. which is often a problem with its bearing capacity has poor characteristics such as clay soil to silty which is easy to experience expansive or bloated process of shrinkage to water content, low level of permeability (nonporous) and friction between weak grains and even types soil that is easy to liquefaction soil.Some ways to determine the bearing capacity of the soil in accordance with the characteristics of the equipment, each test can produce different test results for the same test object. Because this can occur in the testing procedure and the workings of different tools as well as the main test results target of each equipment in the determination of soil parameters.In this study the tests were carried out by analyzing the characteristics of clay California bearing ratio with Laboratory CBR and Unconfined Compression Test (UCS).